Conclusion: Important Antecedents of Public Policy Innovation as Revealed in a Systematic Literature Review – VI - Glor, Eleanor D (Innovation Journal, 2021)
A systematic literature review (SLR) of antecedents of trailblazing and adoption of public policy innovation was conducted. Many antecedents were found—594. A terminology and classification system for them was therefore developed (unique antecedents-508, grouped antecedents-28, factors-15, clusters-3). Differences among trailblazing/adoption and quantitative/qualitative studies were explored six ways. Eleven grouped antecedents of trailblazing were importantly different from those of adoption, 17 were not. Grouped antecedents of quantitative and qualitative studies were not importantly different and so were used as the standard. Only trailblazing had different antecedents from the other three types of study (adoption, quantitative, qualitative). Eight grouped antecedents were the best indicators of policy innovation. Of the three clusters of antecedents, external and internal cluster grouped antecedents were equally important for all four kinds of study; political cluster antecedents were different for trailblazing. Although there was no one best political indicator (large difference from adoption) for trailblazing, political cluster was more important for trailblazing than adoption. Political cluster was higher (had a higher proportion of mentions) and internal cluster lower for trailblazing; political cluster was lower and internal cluster higher for adoption. The important antecedents for public policy innovation were compared to those for the private/public sector, public process/policy and public/social innovation: Differences were found. The best antecedent indicators of trailblazing of policy innovation identified in the literature were external environment, drivers, obstacles (external) and people (internal).